El maíz de alta lisina en nutrición humana - Pradilla, A.; Linares, F.A.; Francis, Charles Andrew; Fajardo, L. (1971)
Review on the analytical and biological testing of opaque-2 modified colombian corn hybrids in presented. The discovery of flint kernels in segregating ears opens the possibility of developing high lysine varieties with different characteristics which would increase the acceptability of modified maize. Analitical and biological testing of the two phenotypes is presented and discussed